The Rehabilitation of a Hospital: The Transformation of a State Psychiatric Hospital - By, Erin Martz (International Journal of Psychosocial Rehabilitation, 2014)
Several decades of research have indicated that many individuals with a range of psychiatric disorders regain functioning and return to community life. The consumer-driven recovery movement and professional community of researchers and service providers have collaborated to clarify definitions and processes related to recovery from psychiatric disorders, but many questions remain about the implementation of the recovery philosophy in service systems. The present article focuses on experiences of one state psychiatric hospital in its movement toward implementing the recovery model. The following research questions will be the focus of this article: How can psychiatric hospitals sustain a recovery philosophy when individuals have restricted movement and limited choices for the purpose of protecting themselves or others from harm? What have been the successes and the problems experienced by one state psychiatric hospital in its drive to systemically implement a recovery perspective?